Do bank credit rejection and financial education affect financial self-confidence?. Issue 6 (2nd October 2017) - Imarhiagbe, Bernard Owens; Saridakis, George; Mohammed, Anne-Marie
Abstract : Purpose: The purpose of this paper is to examine empirically the determinants of owner manager financial self-confidence. In particular, it estimates the effect of bank credit rejection and financial education (FE) on the financial self-confidence of business owners. Design/methodology/approach: This paper uses data from 2004 and 2008 surveys of 2, 500 UK small and medium sized enterprises (SMEs). An ordered probit estimation is used to measure and assess the effect of bank credit rejection and FE variables on financial self-confidence for the two periods. The authors also explore potential differences in self-confidence between males and females. Findings: The results show that outright bank credit rejection reduces financial self-confidence among owner managers whereas partial bank credit rejection is found to help boost confidence prior to the financial crisis. There is strong evidence that FE increases financial self-confidence. Finally, the authors find no association between gender and reported self-confidence in finance. Research limitations/implications: Entrepreneurs and potential entrepreneurs are encouraged to explore financial literacy and knowledge with a view to increasing their financial self-confidence. This will help SMEs to deal with the banks or other finance providers more efficiently. In addition, better application procedures and information on lending criteria may help SMEs to minimize the probability of bank credit rejection. So the current study has implications for professional bodies as well. The study, however, is restricted to sole proprietor and partnership SMEs and in the UK context only. Practical implications: Financial self-confidence has a progressive effect on entrepreneurship and entrepreneurial venture growth. The financial self-confidence of owner managers can support their entrepreneurial capability in starting and operating one or more businesses. As entrepreneurs successfully start and operate their own businesses, they are contributing to economic development through job creation, employment and tax contribution. Originality/value: This paper makes an original contribution in highlighting the usefulness of FE in boosting financial self-confidence among entrepreneurs and potential entrepreneurs. It is also found that the experience of bank credit rejection reduces entrepreneurs' financial self-confidence.